Commentary: Fluoroquinolone Resistance in Salmonella and the Utility of Perfloxacin Disk Diffusion - Ferric C. Fang (Journal of Clinical Microbiology, 2015)
ABSTRACT Fluoroquinolone resistance is a serious and increasingly common problem in Salmonella . Two companion studies in this issue of the Journal of Clinical Microbiology (E. Deak, R. Skov, J. A. Hindler, and R. M. Humphries, J Clin Microbiol 53:3405–3410, 2015, http://dx.doi.org/10.1128/JCM.01393-15 ; R. Skov, E. Matuschek, M. Sjölund-Karlsson, J. Åhman, A. Petersen, M. Stegger, M. Torpdahl, and G. Kahlmeter, J Clin Microbiol 53:3411–3417, 2015, http://dx.doi.org/10.1128/JCM.01287-15 ) provide data to support the use of perfloxacin disk diffusion as a convenient and inexpensive surrogate laboratory method to detect fluoroquinolone resistance in Salmonella when the direct measurement of fluoroquinolone MICs is not feasible. Recently updated CLSI and EUCAST susceptibility breakpoints will help to optimize clinical outcomes and reduce the likelihood of emergent resistance.